Frontispiece: Exploring the Biocatalytic Potential of Fe/α‐Ketoglutarate‐Dependent Halogenases. Issue 33 (10th June 2020) - Voss, Moritz; Honda Malca, Sumire; Buller, Rebecca
Abstract : Freestanding Fe/α‐ketoglutarate‐dependent halogenases are interesting development targets as they may serve as valuable tools for the synthesis of high‐value compounds. To date, a small number of indole alkaloid and amino acid halogenases have been identified and characterized. Initial enzyme engineering examples indicate that the accessible substrate range of these enzymes may be expanded whereas their throughout biophysical characterization continues to inform about the principles governing the halogenation mechanism. For more information see the Concept article by R. Buller et al. on page 7336 ff.